O PARA-MIM [FOR-ME-NESS] COMO CARACTERÍSTICA UNIVERSAL DA EXPERIÊNCIA CONSCIENTE - César Fernando Meurer (Kínesis, 2018)
Resenha de: ZAHAVI, D.; KRIEGEL, U. For-me-ness: what it is and what it is not. In: DAHLSTROM, D.; ELPIDOROU, A.; HOPP, W. (Eds.) Philosophy of mind and phenomenology: conceptual and empirical approaches. London: Routledge, 2015. P. 34- 53.